Reconfigurable contour beam synthesis using a mechanical FEM surface description of dual offset reflector antenna surfaces - Odendaal, J.W. (Johann Wilhelm) (University of Pretoria, 2013)
Thesis (PhD (Electronic Engineering))--University of Pretoria, 2007.